The silent garden : a parent's guide to raising a deaf child - Ogden, Paul W. (Washington, DC : Gallaudet University Press, 2016)
"For over 30 years, The Silent Garden has offered parents of deaf children the support and unbiased information needed to fully realize their children's potential. This completely revised third edition is a must-have resource that will help parents navigate the complex and unique challenges they face. Accessible, practical, and, above all, open-minded, The Silent Garden educates parents quickly and thoroughly about the many conflicting points of view on what is best for their deaf children. Authors Paul W. Ogden and David H. Smith, who are both deaf, present examples and research that guide parents through often unfamiliar territory. From coping mechanisms for parents to advice on creating healthy home environments, the authors cover a range of topics that impact day-to-day actions and decision-making. The topic of communication is discussed extensively as communication access and language development are crucial not only for intellectual growth, but also for positive family and social relationships. The authors look at American Sign Language, English, and various other modes of communication available to deaf children. Different educational options are presented, and technology--including the debate about cochlear implants--is reviewed. Deaf children with special needs are considered here as well. Each topic is accompanied by real-life stories that offer further insight. Always encouraging, The Silent Garden empowers parents to be the best advocates for their deaf children. Throughout, the authors emphasize that each choice is highly personal, and they stress that all deaf children have the potential to lead rich, productive, and exciting lives"--
"Offers parents of deaf children the support and unbiased information needed to fully realize their children's potential. The completely revised third edition is a must-have resource for parents of deaf children"--
PART ONE: FIRST THINGS FIRST -- Introductions -- Lifeboating: caring for yourself -- PART TWO: THE FAMILY GARDEN -- A healthy family environment -- Some gardening tips -- Your deaf child's siblings -- PART THREE: COMMUNICATING -- So much more than words -- Communication options: an overview -- Opportunities in spoken language -- Opportunities in visual language -- Reading the world -- PART FOUR: OUTSIDE THE GARDEN -- The school environment -- Choosing a school -- Moving toward independence -- Cochlear implants -- Boot camp for parents of deaf children with special needs -- Epilogue: Final thoughts.
Revised edition of The silent garden, 1996.
Includes bibliographical references and index.
104849
Keywords: Deaf children -- Family relationships; Deaf children -- Education; Parenting -- General; Deafness